Conducting Hybrid Training for Teacher Professionalism at SMP Wahid Hasyim Malang - Zahid Zufar At Thaariq; Reno Nurdiyanto; Ummul Karima; Chatur Erisa Putri; Doni Anggoro Dwi Wahyu Utomo; Dany Wijaya Kesuma; Dedi Kuswandi (Journal of Community Practice and Social Welfare, 2023)
This article presents an explanation of the implementation of hybrid training as a form of teacher professional development at Wahid Hasyim Junior High School in Malang. Hybrid training is a pedagogical approach that combines online and face-to-face learning to improve the quality of education and teachers' abilities. This programme is implemented with stages (1) pre-implementation, (2) implementation and (3) post-implementation. The pre-implementation stage is passed by preparing all aspects needed. The implementation stage includes the training process which is conducted online but participants follow it simultaneously in one room. The post-implementation stage is carried out through reflections from the training instructor during the activity. This mode of training is expected to provide opportunities for teachers to explore their learning experiences widely through the application of online learning as exemplified in this training programme.